Gold-Catalyzed Skeletal Rearrangement of 1-[2-(1H-Isochromen-3-yl)aryl]ethanones with Alcohols - Wei, Wen-Ting; Xie, Peng; Xia, Jia-Dong; Xie, Ye-Xiang; Song, Ren-Jie; Xiang, Jian-Nan; Li, Jin-Heng (Synthesis, 2012)
A novel gold-catalyzed skeletal rearrangement of 1-[2-(1H-isochromen-3-yl)aryl]ethanones with alcohols to construct a five-membered carbocycle ring onto aromatic systems has been developed. This method serves as the first example of synthesizing inden-1-ones by a gold-catalyzed skeletal rearrangement strategy.
Keywords: gold; skeletal rearrangement; 1-[2-(1H-isochromen-3-yl)aryl]ethanones; alcohols; inden-1-ones